Strategies for conducting joint operations in AJA - Fathollah Kalantari; Abdollali Porshasb (آینده‌پژوهی دفاعی, 2021)
The implementation of joint operations will increase the overall demand and provide the necessary measures and action in the future. The planning and implementation of joint operations is the result of the integration of the combat capabilities of the four AJA forces, which are completely different in terms of organizational culture, management, operational space and specialized environment, and coordination between them is necessary in carrying out different operations. This research is of applied development type and its method is case-context. The statistical sample size of the research is 74 people. The method of collecting field and library information is that by in-depth analysis of theoretical foundations, the factors affecting the implementation of joint operations are counted and then in the form of a questionnaire using quantitative and qualitative analysis mixed to standardize and localize these factors in the operation environment. Joint Army action has been taken. Based on the research results and using IFE and EFE tools, 103 factors (33 strengths, 20 weaknesses, 29 opportunities and 21 threats) to carry out joint operations in 6 components have been identified and measured, and finally strategies have been developed by SWOT method. Their executive priority has been determined using the QSPM method. The current situation in AJA for joint operations is in the mildly conservative quarter. Therefore, 13 strategies have been developed in order to move from an offensive position to a strong or desirable offensive position.